Developing the competitive advantage of SMEs: A case study of a Chinese local supermarket - Ma, Hui (2013)
This research aims to find the methods to help SMEs in China to obtain competitive advantage. Competitive advantage refers to the advantage that a company has over its competitors, which can generate more profits to the firm, bring more benefits to the customers and it should be hard for its competitors to imitate. There are many small and medium-size enterprises in China that are facing fierce competitions, therefore how to improve the competitive advantage of these companies is crucial for them.